TOXIC AND ECOTOXICOLOGICAL EFFECT OF BLACK SAND OF ARTISANAL MINING IN MADRE DE DIOS - Huamán Paredes, Elsa (2017)
In this work the toxic and ecotoxicological effect of black sand (ANM) from artisanal gold extraction in the department of Madre de Dios was studied. Toxicity Characteristic Leaching Procedure (TCLP) was used to evaluate the toxic effect and with the leachates,acute ecotoxicity tests were performed according to EPA protocol 600 / 3-88 / 029 using test microorganisms, Daphnia Magna neonates , with 24 hours of birth and in seeds of Lactuca Sativa. The quantification of total mercury in ANM samples and in leachates was performed by Inductively Coupled Plasma Atomic Emission Spectroscopy. The values obtained of total mercury in the ANM samples were in the range of 0.1 and> 275 mg/kg of black sand indicating that they exceed the background values by 1000 times. In the leachates the total mercury concentration was in the range of 0.001 and> 2.75 mg/L, some of these values exceed the maximum permissible limits (0.2 mg/L) representing a toxic potential for human health. In the case of the ecotoxic effect on daphnia, it was found that metal mercury in interaction with other metals, such as aluminum, could cause a lethal effect. On the Lactuca Sativa, a greater ecotoxic effect on radicle was determined.